2011
DOI: 10.1186/1479-5868-8-54
|View full text |Cite
|
Sign up to set email alerts
|

Childhood and adolescent predictors of leisure time physical activity during the transition from adolescence to adulthood: a population based cohort study

Abstract: BackgroundFew studies have investigated factors that influence physical activity behavior during the transition from adolescence to adulthood. This study explores the associations of sociodemographic, behavioral, sociocultural, attitudinal and physical factors measured in childhood and adolescence with physical activity behavior during the transition from adolescence to adulthood.MethodsChildhood and adolescent data (at ages 7-15 years) were collected as part of the 1985 Australian Health and Fitness Survey an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(88 citation statements)
references
References 45 publications
3
77
0
8
Order By: Relevance
“…Estos resultados son congruentes con otros estudios en universitarios en los que las mujeres presentaban una mayor prevalencia de barreras que los hombres en falta de tiempo, falta de habilidades y en el contexto de práctica (Martínez-Lemos et al, 2014;Ramírez-Vélez et al, 2015). Estos resultados pueden ser debidos a que las mujeres suelen sentirse menos competentes en las clases de EF a lo largo de la etapa infantil y adolescente, por lo que no obtienen experiencias muy positivas, lo que pueden generar más barreras referentes a la capacidad de disfrute en la etapa joven adulta (Jose, Blizzard, Dwyer, McKercher, & Venn, 2011;Mitchell, Gray, & Inchley, 2013). Otra posible justificación a los hallazgos encontrados en las barreras referentes al tiempo, es que las mujeres universitarias le otorgan una mayor importancia a su tiempo de ocio y otras actividades sociales y aficiones personales, a diferencia de los hombres, que suelen decantarse por actividades más deportivas (Pavón & Moreno, 2008).…”
Section: Discussionunclassified
“…Estos resultados son congruentes con otros estudios en universitarios en los que las mujeres presentaban una mayor prevalencia de barreras que los hombres en falta de tiempo, falta de habilidades y en el contexto de práctica (Martínez-Lemos et al, 2014;Ramírez-Vélez et al, 2015). Estos resultados pueden ser debidos a que las mujeres suelen sentirse menos competentes en las clases de EF a lo largo de la etapa infantil y adolescente, por lo que no obtienen experiencias muy positivas, lo que pueden generar más barreras referentes a la capacidad de disfrute en la etapa joven adulta (Jose, Blizzard, Dwyer, McKercher, & Venn, 2011;Mitchell, Gray, & Inchley, 2013). Otra posible justificación a los hallazgos encontrados en las barreras referentes al tiempo, es que las mujeres universitarias le otorgan una mayor importancia a su tiempo de ocio y otras actividades sociales y aficiones personales, a diferencia de los hombres, que suelen decantarse por actividades más deportivas (Pavón & Moreno, 2008).…”
Section: Discussionunclassified
“…In addition to providing information on the contribution of physical activity to bone mass, this study also provides information on psychosocial attitudes to exercise which have implications for bone health across their entire lifespan. Aspects of the relationship between physical activity in childhood and later in adolescence and adulthood have previously been described by others [40][41][42], with physical activity level in childhood considered a predictor of physical activity later in life. Our results support this line of argument and draw attention to the importance of a physically active childhood in relation to bone health.…”
Section: Discussionmentioning
confidence: 99%
“…Previous tracking studies have reported, in general, low to moderate correlation between childhood and adult PA and fitness, with some equivocal results between different domains of youth PA. [8][9][10][11] This might be due to methodological issues as well as small sample sizes. Follow-ups are mainly performed over the early parts of the adult life span, up to 26-39 years, 9,10,12,13 with limited long-term follow-ups from childhood to late adulthood. In addition, little is known about the effects of youth PA and cardiovascular risk later in life.…”
mentioning
confidence: 99%